2020
DOI: 10.2147/rmhp.s254625
|View full text |Cite
|
Sign up to set email alerts
|

<p>Knowledge of and Attitude Toward Leprosy in a Leprosy Endemic District, Eastern Ethiopia: A Community-Based Study</p>

Abstract: Introduction: Leprosy or Hansen's disease is a potentially disabling disease that results in discrimination and self-stigma. A delay in case detection among leprosy patients is one of the factors resulting in disability. Although poor insights of the community toward leprosy lead to delays in case detection, studies on such matters are neglected in Ethiopia. Objective: To assess the level of community knowledge and attitudes toward leprosy in Fedis District, Eastern Ethiopia. Methods: A community-based cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 11 publications
3
15
1
Order By: Relevance
“…It also reflects inadequate monitoring in the national leprosy control program [ 13 ] and the ongoing transmission of leprosy has not been interrupted [ 26 ]. Unfavorable attitude toward leprosy among the community in the same study setting [ 32 ] contributes to late presentation [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also reflects inadequate monitoring in the national leprosy control program [ 13 ] and the ongoing transmission of leprosy has not been interrupted [ 26 ]. Unfavorable attitude toward leprosy among the community in the same study setting [ 32 ] contributes to late presentation [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a higher prevalence of leprosy is expected in this district. Also, the unfavorable attitude in the general community in Fedis District and the stigma favors the hiding of patients from the diagnosis, irrespective of their sex and contact history [ 32 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study were supported by (Masrizal et al 2020) who said that knowledge has a risk of 9.0 for the incidence of leprosy in Padang Pariaman. It is supported by (Urgesa et al 2020) that knowledge has a significant relationship with the incidence of leprosy, with an OR of 1.68. The researcher's assumption is that the incidence of leprosy in the community can occur due to a lack of knowledge.…”
Section: Resultsmentioning
confidence: 87%
“…[ 10 ] A study done in Eastern Ethiopia found that 56.91% had high knowledge of leprosy. [ 11 ] A study conducted by Mohite RV et al . in a rural community in Karad reported that nearly 79% of respondents had good knowledge and 69% had a positive attitude towards leprosy.…”
Section: Discussionmentioning
confidence: 99%